The Association of Thyroid Hormone Changes with Inflammatory Status and Prognosis in COVID-19 - Ceyda Dincer Yazan; Can Ilgin; Onur Elbasan; Tugce Apaydin; Saida Dashdamirova; Tayfun Yigit; Uluhan Sili; Aysegul Karahasan Yagci; Onder Sirikci; Goncagul Haklar; Hulya Gozu (International Journal of Endocrinology)
Background. COVID-19 infection may have multiorgan effects in addition to effects on the lungs and immune system. Recently, studies have found thyroid function abnormalities in COVID-19 cases which were interpreted as euthyroid sick syndrome (ESS) or destructive thyroiditis. Therefore, in this study, we aimed to evaluate the thyroid function status and thyroid autoimmunity in COVID-19 patients. Material and Method. 205 patients were included. The medical history and laboratory parameters at admission were collected from medical records. Serum thyroid-stimulating hormone (TSH), free thyroxine (FT4), free triiodothyronine (FT3), thyroid peroxidase antibody, and thyroglobulin antibody were measured, and patients were classified according to thyroid function status. Results. 34.1% of the patients were euthyroid. Length of hospitalization (p<0.001), rate of oxygen demand (p<0.001), and intensive care unit (ICU) admission (p=0.022) were lower, and none of the euthyroid patients died. 108 (52.6%) patients were classified to have ESS, 57 were classified as mild, and 51 were moderate. The inflammatory parameters were higher in patients with moderate ESS. In cluster analysis, a high-risk group with a lower median FT3 value (median = 2.34 ng/L; IQR = 0.86), a higher median FT4 value (median = 1.04 ng/dL; IQR = 0.33), and a lower median TSH value (median = 0.62 mIU/L; IQR = 0.59) included 8 of 9 died patients and 25 of the 31 patients that were admitted to ICU. Discussion. Length of hospitalization, oxygen demand, ICU admission, and mortality were lower in euthyroid patients. Moreover, none of the euthyroid patients died. In conclusion, evaluation of thyroid function tests during COVID-19 infection may give information about the prognosis of disease.